Pengenalan Biota Laut dalam Bahasa Inggris untuk Pendidikan Anak Usia Dini pada Paud YPPK Kristus Juru Selamat - Ermy Dikta Sumanik; Axelon Samuel Renyaan (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
Early introduction to the marine environment is one of the activities to introduce and maintain the marine ecosystem for children. This community service activity was carried out at PAUD YPPK Kristus Juruslamat Kotaraja by means of socialization, watching videos related to marine biota and direct Q&A with children. The results of this community service activity were that the children were very enthusiastic about learning in the introduction of marine biota using English, increasing children's English vocabulary, increasing children's concern for the marine ecosystem